(untitled) (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2023)
Psychological aspects of learning a foreign language The factors influencing on the successful studying of a foreign language are viewed in the article. The author shows their correlation and influence on the process of studying of a foreign language. The methodical and psychological aspects of studying of a foreign language are examined in the article.